Grievances on Islamic banks: a survey / Ahmad Shaharudin Abdul Latiff, Haryani Haron and Muthukkaruppan Anamalai - Abdul Latiff, Ahmad Shaharudin; Haron, Haryani; Anamalai, Muthukkaruppan (Division of Research and Industry Linkages, UiTM Melaka, 2014)
There have been numerous complaints and grievances by the customers of the Islamic banks. The banks are being accused of charging high financing costs on their customers. Before remedial action could be undertaken, the root causes of the grievances need to be identified. As such, a comprehensive content analysis of literatures pertaining to the grievances on the Islamic banks has been carried out the outcome of the analysis is a cause-effect concept map outlining thirty-four root causes of the grievances. The root causes are further classified under four main causes of grievances: the preference of the banks on debt-based financings, inadequate understanding about the banking-products,-doubts-whether the banks really employ with the Shariah, and poor product innovations and service quality at the banks. The findings of this survey could be viewed as the basis for remedial actions to be undertaken by the Islamic banks to address the prevailing grievances.